Masculinities, practices and meanings: A critical analysis of recent literature on the use of performance- and image-enhancing drugs among men. (November 2020) - Moore, David; Hart, Aaron; Fraser, Suzanne; Seear, Kate
The use of performance- and image-enhancing drugs (PIEDs) has been a topic of considerable research interest since the 1980s, with the vast majority of PIED consumers being men. In this article, our departure point is a 2005 article by Helen Keane, in which she critically analyses 'the discursive constitution of male steroid users' as psychologically disordered subjects. We extend Keane's insightful feminist analysis by examining the constitution of masculinity in post-2005 social science research on PIEDs. We ask (1) to what extent do the discursive trends identified by Keane persist in the more recent literature on PIED use among men? (2) how have her insights been taken up in the post-2005 literature, and (3) to what extent does this work attend to the specificity and varied meanings of steroid practices? We argue that men who use PIEDs continue to be pathologised as insecure, inadequate and vulnerable, and marked by 'obsession', 'compensatory behaviours' and crisis. In some of the analysed texts, the male steroid user becomes doubly disordered as both insecure in his masculine body and at risk of drug dependence. Of the articles that engage with Keane's work, only two recognise the value of her insights. The others misinterpret or apply Keane's argument in inconsistent or incoherent ways. Finally, in some of the post-2005 texts, we begin to see attention to the wide variety of practices and meanings encompassed by the term 'PIED use' although much remains to be learned.